Alberto da Veiga Guignard modernidade e tradição - Palhares, Taisa Helena P. (Editora UNICAMP, 2022)
Alberto da Veiga Guignard (b. Brazil 1896-1962) was a painter of social festivities of São João and of biblical scenes and bucolic landscapes of Minas Gerais as well landscape paintins strongly influenced by asian art. This study aims to investigate the origins of Guignard's artistic production, from his European formation to the dialogue he established with the Brazilian artistic milieu from the late 1920s, in order to broaden the understanding of the modern meaning of his work. Taisa Palhares is a professor of aesthetics at the Department of Philosophy of the Institute of Philosophy and Human Sciences at Unicamp. She was a researcher and curator at the Pinacoteca do Estado, in São Paulo (2005-2015), and has been an art critic since 2000. She received the Jabuti Award for the organization of the book Brazilian Art at the Pinacoteca do Estado de São Paulo (2010). She is the author of several essays on modern and contemporary Brazilian art, as well as the book Aura: the crisis of art in Walter Benjamin (2006)
Keywords: Guignard, Alberto da Veiga -- 1896-1962; Guignard, Alberto da Veiga / 1896-1962 / Criticism and interpretation; Art / 20e siècle